Bioprintable Lung Extracellular Matrix Hydrogel Scaffolds for 3D Culture of Mesenchymal Stromal Cells - Falcones, Bryan (Polymers (Basel), 2021)
Mesenchymal stromal cell (MSC)-based cell therapy in acute respiratory diseases is based on MSC secretion of paracrine factors. Several strategies have proposed to improve this are being explored including pre-conditioning the MSCs prior to administration. We here propose a strategy for improving the therapeutic efficacy of MSCs based on cell preconditioning by growing them in native extracellular matrix (ECM) derived from the lung. To this end, a bioink with tunable stiffness based on decellularized porcine lung ECM hydrogels was developed and characterized. The bioink was suitable for 3D culturing of lung-resident MSCs without the need for additional chemical or physical crosslinking. MSCs showed good viability, and contraction assays showed the existence of cell–matrix interactions in the bioprinted scaffolds. Adhesion capacity and length of the focal adhesions formed were increased for the cells cultured within the lung hydrogel scaffolds. Also, there was more than a 20-fold increase of the expression of the CXCR4 receptor in the 3D-cultured cells compared to the cells cultured in plastic. Secretion of cytokines when cultured in an in vitro model of lung injury showed a decreased secretion of pro-inflammatory mediators for the cells cultured in the 3D scaffolds. Moreover, the morphology of the harvested cells was markedly different with respect to conventionally (2D) cultured MSCs. In conclusion, the developed bioink can be used to bioprint structures aimed to improve preconditioning MSCs for therapeutic purposes.